2020
DOI: 10.1002/jnr.24603
|View full text |Cite
|
Sign up to set email alerts
|

The placenta‐brain‐axis

Abstract: All mammalian species depend on the placenta, a transient organ, for exchange of gases, nutrients, and waste between the mother and conceptus. Besides serving as a conduit for such exchanges, the placenta produces hormones and other factors that influence maternal physiology and fetal development. To meet all of these adaptations, the placenta has evolved to become the most structurally diverse organ within all mammalian taxa. However, commonalities exist as to how placental responses promote survival against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
91
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(101 citation statements)
references
References 122 publications
3
91
0
7
Order By: Relevance
“…Recently, the importance of gut microbiome metabolism of TRP for gut–brain axis has been described ( Kaur et al, 2019 ; Gao et al, 2020 ). Similarly, placental metabolism of TRP might form a crucial component of the placenta–brain axis ( Rosenfeld, 2020a , b ). Considering the large spectrum of TRP metabolites and their roles in pregnancy, it is important to elucidate and understand the shifts in enzyme/transporter expression/activity occurring during gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the importance of gut microbiome metabolism of TRP for gut–brain axis has been described ( Kaur et al, 2019 ; Gao et al, 2020 ). Similarly, placental metabolism of TRP might form a crucial component of the placenta–brain axis ( Rosenfeld, 2020a , b ). Considering the large spectrum of TRP metabolites and their roles in pregnancy, it is important to elucidate and understand the shifts in enzyme/transporter expression/activity occurring during gestation.…”
Section: Introductionmentioning
confidence: 99%
“…The placenta is involved in hormone and neurotransmitter production and transfer of nutrients to the fetus, thus having direct influence on brain development. This intimate connection between the placenta and the brain is termed the placenta-brain axis [6,7]. Epidemiological and animal studies have linked genomic and epigenomic alterations in the placenta with neurodevelopmental disorders and normal neurobehavioral development [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Markers of Autism Risk in Babies: Learning Early Signs (MARBLES) study has identified a differentially methylated region containing a putative fetal brain enhancer in placentas from children diagnosed with ASD (N = 24) compared to placentas from typically developing (N = 23) children [11]. The study of molecular interactions within and between the transcriptome and epigenome that represent the placenta-brain axis may advance our understanding of fetal mechanisms involved in aberrant neurodevelopment [6].…”
Section: Introductionmentioning
confidence: 99%
“…The placenta is involved in hormone and neurotransmitter production and transfer of nutrients to the fetus, thus having direct influence on brain development. This connection between the placenta and the brain is termed the placenta-brain axis [6]. Epidemiological and animal studies have linked genomic and epigenomic alterations in the placenta with neurodevelopmental disorders and normal neurobehavioral development [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, identifying genomic signatures of risk for neurodevelopmental disorders such as ASD in placenta is a challenging. Further study of molecular interactions representing the placenta-brain axis may advance our understanding of fetal mechanisms involved in aberrant neurodevelopment [6].…”
Section: Introductionmentioning
confidence: 99%